EFEKTIFITAS KOORDINASI PERENCANAAN PEMBANGUNAN DESA DI KECAMATAN BOLAANG TIMUR KABUPATEN BOLAANG MONDONDOWâ€. - MAKALALAG, LAZUARDI (Sam Ratulangi University, 2013)
ABSTRACT :To achieve harmony , synchronization and integration of all program / development activities undertaken by the village government and village communities , it is necessary to coordinate the planning of rural development . But the reality shows that the coordination of many rural development planning has not been effective . This study aimed to determine how effective coordination of development planning in rural districts of East Bolaang Bolaang Bolaang .This study uses qualitative methods . Informants drawn from various parties related to development planning in the rural village heads , BPD , LPM , PKK , social organizations in the village , and the village residents . A total number of 20 informants . Primary data were collected by interview .. Analysis using qualitative analysis of interactive models .Based on the results of the study conclude : ( 1 ) Coordination with village planning is done effectively through rural development planning involving stakeholders such as BPD , Institute of Rural Community ( LPM , PKK ) , organization / community groups , and leaders / community leaders . ( 2 ) The effectiveness of coordination of rural development planning is demonstrated by several things: ( a) the plan of development programs in general are set in accordance with the aspirations and needs of the local community , and ( b ) plan development programs are generally set shows alignment , synchronization , and integration , as well as interrelated and mutually supportive ; ( c ) plan development programs set in general can be implemented in an orderly , organized and smoothly .Departing from the results of this penellian then suggested : ( 1 ) For more effective coordination of development planning in the village , the village head held in accordance with the authority should be able to contribute to the fullest ; ( 2 ) For more effective coordination of development planning in the village so it will need cooperation which either of the parties relating to rural development planningKeywords: Effectiveness, Coordination, Planning